Men who pay for sex in Spain and condom use: prevalence and correlates in a representative sample of the general population. Issue 3 (13th March 2008) - Belza, M J; de la Fuente, L; Suárez, M; Vallejo, F; García, M; López, M; Barrio, G; Bolea, Á; ,
Abstract : Objective: To estimate the percentage of men who have paid for heterosexual sex in Spain and the percentage who used condoms. To identify the main factors associated with these behaviours and to describe opinions about condoms. Methods: Sexual behaviour probability sample survey in men aged 18–49 years resident in Spain in 2003 (n = 5153). Computer-assisted face to face and self interview was used. Bivariate and multivariate logistic regression analyses were performed. Results: 25.4% (n = 1306) of the men had paid for heterosexual sex at some time in their lives; 13.3% (n = 687) in the last 5 years and 5.7% (n = 295) in the last 12 months. In the logistic analysis this behaviour was associated with older age, lower education, being unmarried, foreign birth, being a practicing member of a religious group, unsatisfactory communication with parents about sex, age under 16 years at first sexual intercourse and having been drunk in the last 30 days. Of the men who had paid for sex in the previous 5 years, 95% (n = 653) had used a condom in the most recent paid contact. In the multivariate analysis, not using a condom was associated with age over 30 years and first sexual intercourse before age 16 years. Men who did not use condoms in the last commercial intercourse had more negative opinions about condoms. Conclusions: The prevalence of paying for heterosexual sex among Spanish men is the highest ever described in developed countries. The many variables associated with paying for sex and condom use permit the characterisation of male clients of prostitution and should facilitate targeting HIV prevention policies.